2010 IEEE Network Operations and Management Symposium - NOMS 2010 2010
DOI: 10.1109/noms.2010.5488489
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian decision aggregation in collaborative intrusion detection networks

Abstract: Cooperation between intrusion detection systems (IDSs) allow collective information and experience from a network of IDSs to be shared for improving the accuracy of detection. A critical component of a collaborative network is the mechanism of feedback aggregation in which each IDS makes an overall security evaluation based on peer opinions and assessments. In this paper, we propose a collaboration framework for intrusion detection networks (CIDNs) and use a Bayesian approach for feedback aggregation by minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…A collaborative framework for intrusion detection networks (CIDNs) that uses a Bayesian approach for feedback aggregation was proposed by Fung et al [9]. The approach was designed to solve the problem of traditional intrusion detection systems such as host-based intrusion detection system and network-based intrusion detection system, which can easily be compromised by new or unknown attacks.…”
Section: Related Workmentioning
confidence: 99%
“…A collaborative framework for intrusion detection networks (CIDNs) that uses a Bayesian approach for feedback aggregation was proposed by Fung et al [9]. The approach was designed to solve the problem of traditional intrusion detection systems such as host-based intrusion detection system and network-based intrusion detection system, which can easily be compromised by new or unknown attacks.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results demonstrated that the Dirichlet-based approach could enhance both robustness and efficiency. As feedback aggregation is a key component in a trust model, they further applied a Bayesian approach for feedback aggregation to minimize the combined costs of missed detection and false alarms [12]. Their experiments indicated that the Bayesian approach could make an improvement on the true positive detection rate and a reduction in the average cost.…”
Section: • Most Previous Filtration Mechanisms Attempt To Analyzementioning
confidence: 99%
“…In this work, our motivation is thus to design a collaborative trust-based packet filter, which can work effectively in a collaborative network and provide robust trust computation through calculating the IP trustworthiness in a collaborative way. Moreover, we adopt the theoretical CIDN model from the existing literature (e.g., [10], [11], [12]) and modify it according to our requirements. In the evaluation, we mainly compare our approach to similar trust models in defending against betrayal attacks.…”
Section: • Most Previous Filtration Mechanisms Attempt To Analyzementioning
confidence: 99%
“…Our CIDN is based on a distributed collaboration model. In our previous work, Bayesian decision model [26] has been used to make optimal cost decisions based on feedbacks from IDS peers. In this paper, we adopt a more rigorous hypothesis testing model to aggregate feedback from multiple sources and obtain bounds on the number of acquaintances for achieving certain performance goals.…”
Section: Related Workmentioning
confidence: 99%